Anti-inflammatory Effect of Tamarillo (Solanum betaceum Cav.) Fruit Peel Ethanol Extract: Study of Carrageenan-Induced Buccal Mucosa on Rats - Syarafina, Amiretta; Sudiono, Janti (Majalah Patologi Indonesia, 2023)
Background Inflammation is a local protective response by tissue damage. Tamarillo fruit peel ethanol extract has flavonoid as anti-inflammatory, anti-oxidant, inhibit cyclooxygenase and lipoxygenase as well as leukocyte accumulation. This study aims to determine anti-inflammatory effect of Tamarillo fruit peel ethanol extract on carrageenan-induced buccal mucosa of rats. Methods Extraction was done by maceration with 70% ethanol. The 30 rats divided into five groups, namely positive control (diclofenac sodium), negative control (NaCl), and extract doses of 70, 140 and 280 mg/kgBW. Carrageenan was injected as inflammation inducer in the right buccal mucosa. Macroscopic and microscopic observations were performed at three times, 24, 48, and 72 hours after carrageenan injection. Results At 24 hours, inflammatory cells of 70 mg/kg extract were 37, at 140 and 280 mg/kgBW were 18; positive and negative control as 35 and 405. At 48 hours, inflammatory cells of positive control were 22; extract of 70, 140, and 280 mg/kgBW were 21, 17, and 16 while negative control was 26. At 72 hours, positive and negative controls were 18 and 27. Extract of 70, 140, and 280 mg/kgBW had 20, 12 and 9 cells. Extract groups had no significant differences with the positive control (p>0.05) except for the 48th hours of 70 mg/kgBW however the extract groups showed significance with negative control (p<0.05). The lowest number cells (6) was at 280 mg/kgBW on 72 hours. Conclusion Tamarillo fruit peel ethanol extract is effective anti-inflammatory agent especially dose of 280 mg/kgBW on 72 hours.